Educational management and performance of teachers in a public school by agreement - Medina Cuadros, Jovita Rosario (2022)
The management of schools has gained research interest, since it involves the improvement and innovation of teaching and institutional practice as evidence of the work performance carried out. In this sense, the objective of the research was to determine the relationship between educational management and the performance of teachers in a public school by agreement. It was based on a quantitative, basic correlational study and it was possible to count on the voluntary participation of 70 teachers from a state school in Lima who were surveyed using two questionnaires without any inconvenience. The findings of the study showed that in educational management the community dimension that involves collective participation is in the process of improvement and in the case of performance, interpersonal relationships constitute a challenge to be strengthened for the benefit of educational quality and good treatment in teachers as managers. Therefore, it was concluded that there was an urgent need to implement educational management in terms of pedagogical leadership that promotes the involvement of teachers and administrators in the various school matters and activities planned in advance.